A comparison of standard scientific methods and pastoralists’ perceptions of vegetation responses to livestock exclusion in Namaqualand, South Africa - Snyman, Dirk (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.